Type V collagen-induced nasal tolerance prevents lung damage in an experimental model: new evidence of autoimmunity to collagen V in COPD - Robertoni, Fabíola Santos Zambon; Velosa, Ana Paula Pereira; Oliveira, Luana de Mendonça; Almeida, Francine Maria de; Silveira, Lizandre Keren Ramos da; Queiroz, Zelita Aparecida de Jesus; Lobo, Thays de Matos; Contini, Vitória Elias; Baldavira, Camila Machado; Carrasco, Solange; Fernezlian, Sandra de Morais; Sato, Maria Notomi; et al. (Frontiers in Immunology, 2024)
Background Chronic obstructive pulmonary disease (COPD) has been linked to immune responses to lung-associated self-antigens. Exposure to cigarette smoke (CS), the main cause of COPD, causes chronic lung inflammation, resulting in pulmonary matrix (ECM) damage. This tissue breakdown exposes collagen V (Col V), an antigen typically hidden from the immune system, which could trigger an autoimmune response. Col V autoimmunity has been linked to several lung diseases, and the induction of immune tolerance can mitigate some of these diseases. Evidence suggests that autoimmunity to Col V might also occur in COPD; thus, immunotolerance to Col V could be a novel therapeutic approach. Objective The role of autoimmunity against collagen V in COPD development was investigated by analyzing the effects of Col V-induced tolerance on the inflammatory response and lung remodeling in a murine model of CS-induced COPD. Methods Male C57BL/6 mice were divided into three groups: one exposed to CS for four weeks, one previously tolerated for Col V and exposed to CS for four weeks, and one kept in clean air for the same period. Then, we proceeded with lung functional and structural evaluation, assessing inflammatory cells in bronchoalveolar lavage fluid (BALF) and inflammatory markers in the lung parenchyma, inflammatory cytokines in lung and spleen homogenates, and T-cell phenotyping in the spleen. Results CS exposure altered the structure of elastic and collagen fibers and increased the pro-inflammatory immune response, indicating the presence of COPD. Col V tolerance inhibited the onset of emphysema and prevented structural changes in lung ECM fibers by promoting an immunosuppressive microenvironment in the lung and inducing Treg cell differentiation. Conclusion Induction of nasal tolerance to Col V can prevent inflammatory responses and lung remodeling in experimental COPD, suggesting that autoimmunity to Col V plays a role in COPD development.